PENGARUH PERBEDAAN KONSENTRASI ZAT PENGATUR TUMBUH ZPT TERHADAP PERTUMBUHAN BIBIT OKULASI KARET (Hevea brasiliensis) PB 260 DI PERSEMAIAN BANJARBARU - Suliyadi Suliyadi; Emmy Winarni; Eny Dwi Pujawati (Universitas Lambung Mangkurat, 2020)
This study aims to determine the live percentage of rubber grafting seeds in each treatment, analyzing the effect of ZPT concentration on growth and concentration of ZPT which gives the best growth against grafting seeds. Data analysis using Completely Randomized Design (RAL) with 4 treatments and repeated as many as 10 times, which amounted to 40 units of experiments. The time required for this study is ± 3 months. The equipment used is ruler, plastic label, polybag, sprinkler, camera, computer, stationery and measuring cup while the materials used are rubber grafting seeds PB 260 age 2 months, growth regulators (ZPT), and water. The data obtained from the first observation is done by Smirnov Kolmogorov test to know the normality and for the homogeneity test of variance done by Barlett test. The results obtained from this study is the live percentage of rubber grafting seedlings PB 260 for each treatment 100%. The treatments showed significant effect on leaf number parameter with average value A0 = 8,5, A1 = 9,7, A2 = 12,6 and A3 = 10,5. Based on the difference test the average treatment price of A2 (5ml ZPT / 1 liter of water) significantly different to other treatment. While the height increase of shoots did not show any real effect.Keywords: growth of seedling; PB 260 rubber grafting seedling; growth regulator